Strengthening method by using ultra-high-strength fiber-reinforced concrete panels for a column on the soft first story of a reinforced concrete building. (1st March 2023) - Lim, Su A; Tani, Masanori; Watanabe, Hidekazu; Mukai, Tomohisa; Nishimura, Eiichirou; Hori, Shinsuke; Hattori, Tsubasa; Matsumoto, Daisuke; Nishiyama, Minehiro
Highlights: Column on the soft first storey of the RC building damaged by the earthquake. Column strengthened with ultra-high-strength fiber-reinforced concrete (UFC) panels. Cyclic lateral loading test with varying axial load on five 1/3 scale specimens. Maximum strength evaluation method of the specimens strengthened with UFC panels. Proposed strengthening methods improve the seismic performance of the target column. Abstract: This paper presents a simple and efficient strengthening method by using ultra-high-strength fiber-reinforced concrete (UFC) panels on the soft first storys of reinforced concrete (RC) buildings at the risk of story collapse or shear failure of column due to earthquakes. Five 1/3 scale specimens, which replicated RC columns on the soft first story of a 10-story condominium building heavily damaged by the 2016 Kumamoto Earthquake, were constructed and tested. One of these was a reference specimen (no strengthening), and the other four were strengthened by attaching UFC panels on the two faces parallel to the assumed loading direction with or without an UFC or a RC wing wall on either column side. Cyclic lateral and varying axial loads were applied to the specimens to emulate earthquake loads. Load–deformation hysteretic responses, failure modes, and the responses of the UFC panels and the wing walls, are discussed in detail. The experimental results revealed that the reference specimen (without strengthening) had a low-load-carrying capacity and exhibited brittle shear failure, as observed in the actual building during the earthquake. Conversely, the strength and deformation capacities of the strengthened specimens improved considerably, and the effectiveness of the proposed strengthening method was validated quantitatively.